Adolescencja współczesnej kultury zachodniej –kryzys tożsamościowy i sekularyzacja - Marcin Kłosowski (Warszawskie Studia Teologiczne)
Description of modern Western culture is especially made from philosophical, sociological and political science perspective. Much less psychology understood as contemporary social science is used for analyzing cultural phenomena. The article uses developmental psychology as a frame for such analysis. The main idea is to compare adolescent crisis with the crisis of modern Western culture. Just as the identity crisis is in the heart of adolescence, the identity crisis is the center of transformation processes in Western culture. In this perspective, secularization may be seen as a manifestation of such crisis and the militant atheism as a manifestation of negative identity. The article also shows how processes attributed to adolescence such as emotional liability, rebellion, undermine authorities, increase of consciousness, and self-knowledge, moral independence and relativity thinking can be correlated with many phenomena associated with Western culture. The point of this text is that one can perceive modern Western culture as being in a process of maturation. There is not only the comparative analysis, but also some practical implications. The article also contains some recent researches analysis from psychology of religion and spirituality perspective related to secularization process in contemporary times.